Antimicrobials in dog‐to‐dog bite wounds: A retrospective study of 1526 dog bite events (1999‐2019) - Nicole J. Kalnins; Justine S. Gibson; Allison J. Stewart; Catriona Croton; Sarah L. Purcell; Bandula Rajapaksha; Mark Haworth (Journal of Veterinary Internal Medicine, 2022)
Abstract Background Although dog‐to‐dog bite wounds (DBW) are common, few studies worldwide have evaluated antimicrobial usage patterns or appropriateness of use. Objectives Report frequency and results of DBW cultures, including antimicrobial susceptibility patterns. Determine the most commonly prescribed antimicrobials and their appropriateness for the treatment of DBW, and if antimicrobial importance is associated with wound severity, clinic type or year. Animals One thousand five hundred twenty‐six dog bite events involving 1436 dogs presenting with DBW from 3 Australian university clinics from 1999 to 2019. Methods Retrospective study. Medical records were reviewed for presenting signs, culture and susceptibility testing, antimicrobial treatment, and outcome. A partial proportional odds model was used to determine if use of higher importance antimicrobials was associated with wound severity, clinic, or year. Results Antimicrobials were prescribed in 88.1% (1344/1526) of DBW. Amoxicillin‐clavulanic acid was prescribed in 73.4% (1121/1526) of dogs, followed by first‐generation cephalosporins, 18.1% (277/1526). Of a total of 1647 antimicrobial prescriptions, underdosing occurred in 13.4% for AMC (220/1647) and 26.1% (81/310) of dogs prescribed first generation cephalosporins. There was an association between the increased use of high‐importance antimicrobials and wound severity (P < .001), antimicrobial polytherapy (P < .001) and year (P < .001). The odds of the clinic with specialists prescribing high‐importance antimicrobials compared to those of medium importance for DBW was 82% less than that of a semi‐rural, mixed and general practice. Culture and susceptibility (C&S) testing was performed in 1.8% of dogs. Conclusion and Clinical Importance Empirical use of amoxicillin‐clavulanic acid was common for DBW. Increasing wound severity was associated with greater use of high‐importance antimicrobials. While C&S testing was rarely performed, routine susceptibility profiles are recommended to optimize antimicrobial stewardship.